Implementation STEAM project-based learning to improve the students’ critical thinking skills - Zainatul Hasanah; Erlia Hanum; Cut Roswita; Rahmawati Rahmawati (International Journal on Education Insight, 2026)
The lack of students’ critical thinking skills has been widely reported, particularly in biology learning, which often emphasizes memorization rather than higher-order thinking processes. Although various instructional approaches have been proposed, limited studies have specifically examined the integration of STEAM-based project-based learning (PjBL) to address this issue. This gap indicates the need for empirical evidence on how such an approach can effectively enhance students’ critical thinking skills. The purpose of this study was to describe the implementation of STEAM-based PjBL to improve students' critical thinking skills on the topic of environmental pollution. It also aimed to capture the significant difference in students' critical thinking skills before and after the application of STEAM-based PjBL, and the ignificant difference in students' critical thinking skills between students who learn using STEAM-based PjBL and students who learn using conventional learning. It was an experiment with the population was all 10th-grade students at SMA Negeri Peusangan, a public senior high school in Aceh, Indonesia. From the population, we purposively selected 140 students as the sample. The differences in critical thinking skills of the experimental class and the control class were analyzed using the independent sample t-test. The results show that the average N-gain for the experimental class of 72.03. The critical thinking skill gain was 0.93. of the paired sample t-test analysis in the experimental class showed a significance value of ρ < .001, indicating that Ha was accepted. This result demonstrates that there was a significant difference in students' critical thinking skills before and after the implementation of the STEAM-based PjBL in the 10th-grade of SMA Negeri Peusangan on the topic of environmental pollution, which means the students’ critical thinking was significantly improved.